Information Literacy as a part of an outreach community program for pre-University Learners in South Africa: a case study. - Zambri, Janet Teresa (Qualitative and Quantitative Methods in Libraries; Vol 3 No 4 (2014): December 2014 Issue, 2017)
This paper is a case study which will explore the process of working in an academic enrichment curriculum as part of an outreach community program for talented pre-University learners. The program supplements the formal school subjects such as mathematics, science, language, in addition the exposing learners to computer science, forensic science, molecular literacy, information literacy and social research.  It will outline the context of the course we offer with the other disciplines.  It will discuss the challenges we faced, the lessons learnt, and our aspirations for the future. The overall aim of the program is “to increase the academic, social and psychological preparation of academically talented learners from socio-economically disadvantaged backgrounds for admission to and success (retention) at South African selective universities.”